Education and Technology Management Policies and Practices in Madarasah - wahyuningsih; Nadia Nur Azizah; Tatik Mariyanti (Pandawan Sejahtera Indonesia, 2022)
In order to promote education in madrasahs, this study seeks to assess policies from a sociopolitical perspective. This research, it continues, was carried out using a descriptive qualitative method to the kind of library research, with book data serving as the data source. Content analysis, whose scope includes the depth of information content, was used to carry out the data analysis technique. The findings demonstrated that madrasah-based management involves the principal and is participatory management of the madrasah. The community, stakeholders, instructors, and students must work together to attain the goals for educational quality. Since1960–1990, there has been a global push toward decentralization in the area of education reform. The New Order's fall in 1998 ushered in a period of transition that included the constitutional reformation of education in Indonesia. since the Regional Government Law No. 22 of1999, which was later revised by Law No. 32 of the same year, established regional autonomy. In2004, the local government received control of the educational matters.